Satisfaction of patients with cervical pain and low back pain in a rehabilitation service - González Viejo, M.A.; Oyarzabal, A.; Fernández Fernández de Leceta, Z.; Rotinen, J.; Arrizabalaga, N.; Ibáñez de Garayo, E. (Anales del Sistema Sanitario de Navarra, 2008)
Background. The aims of the present paper are: to reduce waiting time for treatment of patients with low back pain/cervical pain; to determine the degree of satisfaction of patients being treated by groups; and to determine whether there is correlation amongst satisfaction, improvement of pain and impact on the activities of everyday life. Methods. Prospective observational study. Study population: users of the surgeries of a tertiary hospital and the specialties center attached to it, who attended surgery because of cervical/low back pain, and practiced a serie of exercises. Period of study: 1 october 2001 to 1 April 2002. The instrument of measurement used for evaluating pain and disability was the Von Korff questionnaire for low back pain, with an adaptation of this questionnaire for cervical pain. Statistical analysis: Wilcoxon’s non-parametric test. Results. Total number of patients 273 (176 with cervical pain and 97 with low back pain): 198 women and 75 men. Average age: 48.5 (20-81). The self perceived evaluation of the patients treated in a group improved in 72 subjects (p<0.0001) with cervical pain and in 33 (p<0.001) with low back pain. Post-treatment pain was significantly better (p<0.001) than pre-treatment pain in both groups. Its influence on the activities of everyday life did not achieve statistical significance. Perception of the information received was positive in the cervical group (p<0.05). Conclusions. Following the application of different techniques: reduction in number of patients and waiting time – decisive factors in the satisfaction of these patients; a good acceptance of group treatment was obtained, ameliorating pain. The degree of knowledge of their pathology only improved in the cervical group.